2012
DOI: 10.1159/000337876
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Access Devices Are Safe and Effective in the Treatment of Posthemorrhagic Ventricular Dilatation prior to Shunt Placement

Abstract: Intraventricular hemorrhage of prematurity (IVH) is a diagnosis that has become more frequent in recent years. Advances in medical care have led to survival of increasingly premature infants, as well as infants with more complex medical conditions. Treatment with a ventricular access device (VAD) was reported almost 3 decades ago; however, it is unclear how effective this treatment is in the current population of premature infants. At our institution (from 2004 to present), we treat posthemorrhagic hydrocephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Their shunting rate is 95%. Notably, Tian et al [17] presented a series of VADs with a 0% infection rate, a very low complication rate and a tapping protocol quite similar to ours; nevertheless, they observed a shunt conversion rate of 70%. We were unable to identify factors that can explain the differences in outcome compared with our series.…”
Section: Vp Shunting Ratesupporting
confidence: 76%
See 1 more Smart Citation
“…Their shunting rate is 95%. Notably, Tian et al [17] presented a series of VADs with a 0% infection rate, a very low complication rate and a tapping protocol quite similar to ours; nevertheless, they observed a shunt conversion rate of 70%. We were unable to identify factors that can explain the differences in outcome compared with our series.…”
Section: Vp Shunting Ratesupporting
confidence: 76%
“…Furthermore, there is no consensus on when to treat PHVD [3], and the optimum PHVD treatment remains unknown but may consist of temporising measures such as acetazolamide and furosemide [15], intraventricular fibrinolytic therapy [22], intermittent lumbar punctures, external ventricular drain (EVD), ventriculo-subgaleal shunting (VSGS), ventricular access devices (VAD) for intermittent CSF taps, neuroendoscopic lavage [4,6] and definitive measures such as ventriculo-peritoneal shunting (VPS) [12]. In a significant number of cases, temporising measures still led to persisting shunt dependency, although shunt dependency rates vary widely (5-95%), with the majority over 70% [1,2,4,6,10,11,13,14,17,[19][20][21]24].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have demonstrated the advantages of placing a temporizing device rather than symptomatic management with serial ventricular taps before permanent VP shunt insertion, guidelines for the use of these devices have not been created. 26 The 2 mainstays are the ventricular reservoir and VSGS, which were compared in this study with respect to short-term outcomes including device infection and VP shunt insertion rates and timing.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study that reported on VSGS mentioned labs, only that they were sent prior to VPS insertion [10]. For VADs, three studies explicitly stated that labs were sent after every aspiration [6,11,12], one study stated that "clinical investigations followed the punctures" [13], three studies from two research groups merely stated that labs were done "routinely" [14][15][16], one study "three times per week" [17], one study "at least once a week" [18], two studies "weekly" [19,20], one study "at 5-to 8-day intervals" [21], and one study just that labs were sent [22]. Assuming labs are obtained every 7 aspirations for institutions that obtain labs on a weekly basis for VADs, labs would be sent at least 3.7 times per VAD patient.…”
Section: Literature Review and Meta-analysismentioning
confidence: 99%